2009
DOI: 10.3182/20090812-3-dk-2006.0076
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model-Based Clinical Sepsis Biomarker for Critically Ill Patients

Abstract: Sepsis occurs frequently in the intensive care unit (ICU) and is a leading cause of admission, mortality, and cost. Treatment guidelines recommend early intervention, however positive blood culture results may take up to 48 hours. Insulin sensitivity (S I ) is known to decrease with worsening condition and could thus be used to aid diagnosis. Some glycemic control protocols are able to accurately identify insulin sensitivity in real-time.Receiver operator characteristic (ROC) curves and cut-off S I values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In particular, a great deal more data entry could be included for other uses, such as tracking organ failure as a response to TGC, 9 monitoring the impact of drug therapy, 32 or using model-based metabolic markers in sepsis or other diagnostics. 33,34 Such possible additions were not in the focus of this case study, but their addition or use could be included using a similar design approach.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a great deal more data entry could be included for other uses, such as tracking organ failure as a response to TGC, 9 monitoring the impact of drug therapy, 32 or using model-based metabolic markers in sepsis or other diagnostics. 33,34 Such possible additions were not in the focus of this case study, but their addition or use could be included using a similar design approach.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more importantly, such model-based SI [19,33,85,109,110,114,117,137,154,161,[165][166][167][168][169][170][171][172][173]] can be monitored and its level and/or variation assessed relative to condition [16,18,19,153,171,[174][175][176][177][178][179][180][181][182]. Thus, if accurate, this value offers not only the potential of good, personalised control, but also further insight into patient condition.…”
Section: Dynamic System Models Of the Metabolic Systemmentioning
confidence: 99%
“…In the critical care arena, the use of in silico physiological models is only emerging. However, there are already model-based or model-derived applications for managing sedation [ 25 , 26 ], cardiovascular diagnosis and therapy [ 27 , 28 ], mechanical ventilation [ 29 , 30 ], and the diagnosis of sepsis [ 31 , 32 ]. Particular to TGC, there are already some attempts at modeling for both understanding and implementing TGC [ 23 , 33 - 42 ], with a review of many in [ 43 ].…”
Section: A Series Of Questionsmentioning
confidence: 99%
“…In intensive care, patient-specific metabolic model parameters also have been used as sepsis biomarkers because they can accurately reflect the inflammatory status of the patient and severity of illness [ 31 , 32 ]. These studies showed that model-based insulin sensitivity alone could provide 70-80% sensitivity and specificity in assessing sepsis compared with a control cohort, yielding a negative predictive value (NPV) greater than 99%, thus clearly identifying periods where antibiotic therapy was not necessary.…”
Section: A Series Of Questionsmentioning
confidence: 99%